Glucose derivative functionalized rice husk biochar for the removal of emerging contaminant through adsorption - Rajandran, Prabu; Wee, Chi Chyin; Siti Fatimah Zaharah, Mohd Fuzi; Lestari, Ajeng Yulianti Dwi; Nasratun, Masngut (Semarak Ilmu Publishing, 2025)
Carbazole (CBZ), recognized as a persistent contaminant with diverse ecotoxicological effects, presents a formidable challenge in its removal from wastewater. This study centers on the utilization of glucose derivative functionalized biochar (GDRB) as an adsorbent for the removal of CBZ. The synthesis of GDRB involved the cross-linking of β-cyclodextrin with rice husk biochar. The primary aim of this research was to evaluate the removal efficiency of CBZ from aqueous solutions using GDRB. In pursuit of thisgoal, a batch mode adsorption was implemented by employing synthetic wastewater spiked with CBZ. Various parameters, including the adsorbent loading, CBZ concentration, and treatment time, were systematically investigated for their influence on CBZ removal, with analysis performed using ultraviolet-visible spectroscopy. The results demonstrated that GDRB exhibited a superior ability to interact and adsorb CBZ compared to the original rice husk biochar. Specifically, GDRB showcased an impressive adsorption capacity of 17.45 mg/g, surpassing the original rice husk biochar (3.0 mg/g) and its activated form (7.0 mg/g) under the optimal GDRB loading of 0.04 g, initial CBZ concentration of 40 mg/L, and treatment time of 210 min. This setting yielded an outstanding CBZ removal efficiency of 87.25%. The findings provide valuable insights into the sustainable application of GDRB for treating emerging contaminants in wastewater.